Family Dinner at Frances Kamp Celebrating Cliff and Evie Macabee's 40th Anniversary - Watkins, Howard::::::::: (1988)
Seated: Adam Watkins Evie Macabee and Robin Watkins; Standing: Howard Watkins, Frances Kamp, Cliff Macabee and Christine Watkins Fran's home at 6300 N. Palm Avenue #109, Fresno